EXPLORING THE PRINCIPAL TEACHINGS OF KHALWATIAH SYEKH YUSUF TARIQAH IN SOUTH SULAWESI - Muhaemin Latif (JICSA : Journal of Islamic Civilization in Southeast Asian, 2020)
This article discusses the principal teachings of Khalwatiah Syekh Yusuf tariqah in South Sulawesi. This tariqah is one of the leading tariqahs in the region since its emergence in the seventeenth century. Khalwatiah Syekh Yusuf has influenced the Muslim's understanding concerning sufism issues. The researcher employs qualitative as a method of research.  The research suggests that Khalwatiah Syekh Yusuf is the integration of different tariqahs which were obtained by Syekh Yusuf during his intellectual journey. The principal teachings of Khalwatiah Syekh Yusuf can be drawn into three elements. They are the concept of inner purity, the understanding of God, and the meaning of insan kamil. These three principal teachings become the foundation of this tariqah as well as become it’s characteristic. Although Syekh Yusuf studied from different Sufis, especially from Ibnu Arabi’s thought, this tariqah is strongly associated with Asyariyah theology that led to this tariqah be a moderate tariqah.